Bride behind the desert veil - Green, Abby (Green, Abby. Marchetti dynasty, 2021)
The stranger at the altar... is the woman he was meant to forget! Sharif Marchetti is deliberate. Controlled. Especially in his strategic choice of a royal bride. So after surrendering to his instincts with a mystery woman, he must erase their desert encounter from his memory. Until they meet a second time... moments before they exchange wedding vows! Princess Aaliyah Mansour is stunned that her arranged marriage is with the man who'd stirred her soul. She was prepared for a union that left her independence and defences intact. Not a jet-set lifestyle with a husband who's the ultimate distraction...